A signal-conditioning chip for accelerometer applications - Lee, Wing Foon (2008)
This thesis presents a low-cost, high-performance, fully-integrated interface and signal-conditioning ASIC (Application-Specific Integrated Circuits) for capacitive-based automotive accelerometers. The ASIC is a mixed-signal system, which comprises a switched-capacitor (SC) sense amplifier, a two-stage (SC and continuous-time) filter, a scaling output stage and a clocking module, with on-chip calibration capability. The design foundation is based on a new "injection-nulling switch" (INS).